2013
DOI: 10.1152/ajprenal.00160.2013
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria-targeted heme oxygenase-1 decreases oxidative stress in renal epithelial cells

Abstract: . Mitochondria-targeted heme oxygenase-1 decreases oxidative stress in renal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 38 publications
0
48
0
Order By: Relevance
“…In the absence of such a phenomenon, the bioenergetics might be more severely compromised. A recent study indicated that expression of HO-1 targeted to mitochondria attenuated oxidative stress (43). These observations, taken together, suggest that mitochondrial translocation of HO-1 could serve as a cytoprotective mechanism against possible mitochondrial dysfunction induced by oxidative or metabolic insults (32).…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 87%
“…In the absence of such a phenomenon, the bioenergetics might be more severely compromised. A recent study indicated that expression of HO-1 targeted to mitochondria attenuated oxidative stress (43). These observations, taken together, suggest that mitochondrial translocation of HO-1 could serve as a cytoprotective mechanism against possible mitochondrial dysfunction induced by oxidative or metabolic insults (32).…”
Section: Effect Of Oxidized Hb Exposure On E10 Cellsmentioning
confidence: 87%
“…While HO-1 localizes predominantly to the endoplasmic reticulum, expression in the nuclear (18,82), mitochondrial (17,21), and secretory (83, 151) subcellular compartments has been reported. In the setting of hypoxia-or heme-mediated oxidative stress in vitro, HO-1 localized to the nucleus and modulated transcription of oxidative stress response genes (82).…”
Section: Cellular Localization Of Ho-1mentioning
confidence: 99%
“…HO-1 targeted to mitochondria was protective against hypoxia-induced oxidative damage in human embryonic kidney cells. Protection was superior in mitochondrial-targeted HO-1 overexpressing cells compared with cytoplasmic overexpression (21). Bindu et al found mitochondrial expression of HO-1 in a rat model of gastric mucosal injury, which protected from mitochondrial stress, improved cellular respiratory function, and prevented apoptosis (17).…”
Section: Cellular Localization Of Ho-1mentioning
confidence: 99%
“…While mitochondrial fission is orchestrated by the dynamin-related protein 1 (DRP1) and the mitochondrial fission 1 (Fis1) protein [34], [35], the fusion process is controlled by the autosomal dominant optic atrophy 1 (OPA1) protein, together with the mitochondrial fusion proteins mitofusion 1 and 2 (Mfn 1 and 2), located on the mitochondrial outer membrane, [36], [37]. As HO-1/HO-2 are known regulators of mitochondrial integrity and function [38], [39], [40], [41], we hypothesized that adipose HO-1 gene is essential for increased mitochondrial fusion that may result in an increase in the beige cell population within adipose tissue or conversion of white adipose function populations and white adipose function that include expression of PGC1α levels and thermogenic genes.…”
Section: Introductionmentioning
confidence: 99%